Nurse's Perception about the Schizophrenic Patients CareNurse's Perception about the Schizophrenic Patients Care in Menur Mental Hospital, East Java Province - Eka Widyaningrum, Dyah; Yusuf, Ahmad.; Dian Tristiana, Rr (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Schizophrenia is a chronic mental disorder that can affect every 1% of the world's population. The unique characteristics of mental patients will affect the pattern of nursing care provision. The task of nurses caring for mental patients can affect the intellectual, emotional, and social environment of nursing because the quality of nursing services for mental patients is influenced by prejudice about mental illness by nurses. This study aims to determine nurse’s perceptions during the patients care with schizophrenia. Method: This study used a qualitative design with 7 nurses working at the mental hospital as samples. They have a job to treat schizophrenia patients. Data was collected by in-depth interviewing and a sociodemographic questionnaire. The method used to analyze was Collaizi's nine-step data interpretation method. Result: The results of the data analysis were categorized as themes. There are three themes obtained from this study: 1) nurses 'views on schizophrenia patients; 2) nurses' emotional responses during treating schizophrenia patients; and 3) the success of the mental nursing process. Conclusion: Nurses’ perceptions during treating schizophrenia patients were influenced by nurses' knowledge and experience during treatment. Every schizophrenia patient was difficult to predict; thus, each nurse should give a different perception.